Efficacy and safety of upadacitinib for patients with immune-mediated inflammatory diseases: a systematic review and meta-analysis - Chai, Rui; Li, Xiaomin; Shen, Wei; Jin, Ziyi; Yao, Genhong; Tang, Xiaojun; Geng, Linyu; Sun, Lingyun (Frontiers in Immunology, 2025)
ObjectiveThere is a growing array of options for the treatment of immune-mediated inflammatory diseases (IMIDs). To explore upadacitinib’s efficacy and safety in autoimmune disease treatment, we conducted this study.MethodsPubmed, Web of Science and Embase were searched for randomized controlled trials related to the treatment of upadacitinib from the databases’ inception to May 31, 2024. After literature screening, data extraction and bias assessment by two investigators, RevMan 5.3 or Stata 17.0 software was used for meta-analysis.Results45 records across the following five types of IMIDs were obtained. For rheumatoid arthritis (RA), upadacitinib 15 mg outperformed placebo, methotrexate and adalimumab (ADA) in 20% improvement according to ACR criteria (ACR20) and 28-joint disease activity score (DAS28) (P < 0.05). It also improved quality of daily life based on pain relief, morning stiffness and 36-Item Short Form Health Survey, etc. For axial spondyloarthritis (axSpA), upadacitinib 15 mg enhanced 20/40% improvement in Assessment of SpondyloArthritis international Society (Risk Ratio [RR] = 1.28/1.47), with better rates of low disease activity and inactive disease as well. For psoriatic arthritis (PsA), upadacitinib 15 mg or 30 mg significantly improved ACR20 compared to placebo (RR = 2.46/2.68, P < 0.001) and reduced psoriasis skin lesions, though it showed no superior benefit for enthesitis compared to placebo. For Crohn’s disease (CD), upadacitinib 45 mg significantly improved stool frequency and abdominal pain score clinical remission compared to placebo (RR = 2.47, 95% CI [2.12, 2.88], P < 0.001) as well as Crohn’s Disease Activity Index score remission and endoscopic response (P < 0.001). For ulcerative colitis (UC), upadacitinib 45 mg increased clinical remission rates (RR = 6.92, 95% CI [4.99, 9.59], P < 0.001) and improved symptoms like bowel frequency and abdominal pain (P < 0.05). Overall adverse events (AEs) rates were generally similar to non-upadacitinib groups (RR = 1.02, 95% CI [0.98, 1.07]). However, the higher risks of infections especially herpes zoster (HZ) must be highlighted in upadacitinib group. Although the incidence of death, serious adverse events (SAEs), and long-term risks like cardiovascular events and malignancies were without statistic significant differences, careful monitoring during treatment would still be essential.ConclusionsUpadacitinib is effective in treating IMIDs like RA, axSpA, PsA, CD, and UC. Though well-tolerated generally, its safety in infection especially HZ needs caution. Thorough assessment, monitoring and individualized dosing are vital to manage potential AEs.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024569370.